REDESCRIPTION OF TWO SPECIES OF GENUS DERMATOXENUS MARSHALL (ENTIMINAE: CURCULIONIDAE: COLEOPTERA) FROM INDIA - G. MAHENDIRAN,; V. V. RAMAMURTHY, (The Bioscan, 2012)
Two species of the genus Dermatoxenus Marshall (1916) (Curculinidae: Entiminae) are revised from India. The generic and species descriptions are updated through addition of measurements, description of elytral vestiture and genitalic characters. These are supported by 35 illustrations including 26 line diagrams. In addition, annotated checklist and a modified key to the species are also provided.